Factores psicosociales predisponentes asociados al bajo rendimiento académico de los estudiantes de 6to grado de la Unidad Educativa Rosaura Maridueña - Alvarado Jiménez, Noemi Carolina (2024)
This project is established as a valuable contribution to the educational field by systematically addressing the psychosocial factors that affect the poor academic performance of 6th grade students at the Rosaura Maridueña Educational Unit. Research is revealed as an essential tool to thoroughly understand the predisposing elements associated with said poor performance, thus allowing the identification and detailed description of crucial characteristics. The choice of the mixed approach methodology is based on its ability to not only explore and describe the complexities of the situation, but also to accurately quantify the data obtained. This methodological strategy provides rigor and depth to the analysis, allowing a holistic understanding of the factors that influence academic performance. Ultimately, the results of this project will not only enrich academic knowledge, but will also offer practical and applicable recommendations to improve the academic performance and psychosocial well-being of 6th grade students, thereby promoting a more enriching and equitable educational environment.